Representasi Kecemburuan Dalam Film Pendek "The Neighbors' Window" - Lambok Hermanto Sihombing; M. Shacrul Fahrezi; Haysel L. A. Nursewan (BASIS (Bahasa dan Sastra Inggris), 2021)
Short films are often underestimated for their lack of duration. People think that the short duration will affect to how the messages are conveyed. However, short films are now very popular. There is even a category of best short film in Academy Awards, or well-known as Oscars. The Neighbors’ Window is one of many Oscars’ winners for best short film. This research aims to find out how jealousy is represented in the short film The Neighbors’ Window by Marshall Curry. This method of this research uses a theory from Saussure called semiotics. This research also uses an approach of Representation theory by Mary Beltran and Stuart Hall. Most of the data in this article is taken from scenes in the short film which later are connected with the theories. This result of this research shows that the important scenes presented in this movie are representation of Jealousy towards each character. This research shows that the movie is about jealousy presented by the symbols in the movie using some analytical research by applying the two theories.